Existence of solution for a generalized Schrödinger–Poisson system via bifurcation theory - Ricardo Alves (Electronic Journal of Qualitative Theory of Differential Equations)
In this paper, we study a generalized Schrödinger–Poisson system in a bounded domain of $\mathbb{R}^{3}$ and involving an asymptotically linear nonlinearity. We prove the existence of positive solutions using bifurcation theory.